Distraksi Menonton Efektif Menurunkan Nyeri Ringan Pasien Congestive Heart Failure (CHF) - Achmad Djamil; Dewi Yuliana; Mia Arini (Jurnal Kesehatan, 2019)
Congestive heart failure (CHF) is a pathophysiological condition in the form of abnormalities in the function of the heart so that the heart is unable to pump blood to meet the needs of tissue metabolism or its ability is only present when accompanied by an abnormally elevated diastolic volume. Providing complementary nursing care with the watch distraction method can help reduce mild to moderate pain in patients with congestive heart failure. The research objective was to determine the effect of distraction watching on mild pain in patients with CHF. The study used a Quasi-Experimental design with one group pre-test post-test design approach. A total sample of 60 respondents was divided into 2 groups and selected using non-probability sampling with the consecutive sampling technique. The results showed that distraction watch therapy had a significant effect on mild pain in patients with CHF. Distraction watch therapy significantly influences mild pain in patients with CHF.